Strengthening International Cooperation to Tackle Indonesian Women Trafficking (Global Focus, 2022)
Problem of trafficking and people smuggling is very difficult to solve. Trafficking and smuggling of people in China for instance, involve routes that are not easy to track, managed by highly organized networks, and long travel distances to cover. Stakeholders searched and found it difficult to find their mode of transportation, which changes over time and very well planned. This research is qualitative in nature by trying to understand the situation in the research subject. This research used a case study in the design and employ primary data that is interview in almost 90 (ninety) percent with key persons that are directly or indirectly linked to the main finding of the research. By using concept combating Indonesian women trafficking, this research concluded that the Indonesian state through Interpol Indonesia has a national interest in combating the number of human trafficking in China district by strengthening international cooperation in providing, liaising, and facilitating the Indonesian women nationals under the international humanitarian crime.